Pitahaya (Hylocereus spp.): a short review - Ortiz-Hernández, Yolanda Donají; Carrillo-Salazar, José Alfredo (Comunicata Scientiae, 2012)
Hylocereus is a native American cactus of varied habits and widely distributed from the Floridacoast to Brazil. The fruit is known under several commercial and native names, but “pitahaya” or“pitaya” prevails all around. The genus contains 14 species and it is part of the subtropical andtropical American rainforests. It is common to find Hylocereus in family gardens in Central America,where it is traditionally used as food and medicine. Commercial plantations are distributed aroundthe world due to its agronomic, industrial and economic importance. Hylocereus species cultivatedaround the world are mainly H. undatus, H. monacanthus and H. megalanthus. Research relatedto Hylocereus has increased significantly in the fields of taxonomy, anatomy, physiology, genetics,biochemistry, medicine, agronomy and industry, but there is still too much to do. This documentdescribes part of Hylocereus history, technological advances and it provides perspectives ofresearch and usage of this emerging crop.